Communicating medication risks in pregnancy: Towards shared decision making - Winterfeld, Ursula; Hodson, Kenneth; Berlin, Maya; Marin, Benoît; Ceulemans, Michael; Weber-Schoendorfer, Corinna; Girardin, François R.; Baud, David; Schaad, Béatrice; Panchaud, Alice (Frontiers in Drug Safety and Regulation, 2025)
Medication use during pregnancy is common, yet safety data remain limited, often leading to exaggerated risk perceptions and suboptimal care. Current communication practices are fragmented: product labeling and patient leaflets tend to emphasize potential harms, while specialized resources are underused. We explore the challenges of conveying accurate risk-benefit information and highlight the need for shared decision making. Integrated, evidence-based resources accessible to both healthcare providers and patients can reduce misinformation, improve adherence to essential treatments, and ultimately enhance maternal and child health. The Swiss MAMA-MEDS initiative illustrates how a unified knowledge base can align messaging, address health inequalities, and support patient-centered pregnancy care.